Evaluation of the livestock sector contribution to small holders in eastern India - DEY, AMITAVA; KAMAL, REENA; BHATT, B P (The Indian Journal of Animal Sciences, 2018)
The eastern region of India occupies about 21.85% of the total geographical area of the country and sustains 1/3rd of the total human and bovine population. Though livestock husbandry support to livelihood security of resource poor farmers’ of the region, however, its synergy in cropping/farming systems has not been defined. Present study was designed to understand the contribution of livestock towards food and nutritional security besides sustaining the crop production system in seven eastern states. The data indicated that livestock and poultry is, by and large, reared in low input system and thereby the productivity of milk, meat and egg is low. Per capita availability of animal products was much lower than the national average. Growth and production efficiency of livestock/birds was influenced significantly by agro-climatic variations. Livestock productivity was comparatively better in Eastern Indo Gangetic Plains (EIGP). EIGP had highest egg and milk production. More than 80% of the total duck egg production is contributed by eastern India alone. Annual supplement of protein and energy was 3–4 fold lower in indigenous livestock/bird population than improved ones. Of the 106 million tonnes of manure, about 90 million is recycled into cropping/farming systems and rest is used as a source of biomass to meet out the domestic energy requirements. The data indicated that animal husbandry is an important food production system in eastern India besides crop production system and both the systems have been found complimentary to one another through emphasis on resource recycling.